Engineering the mangrove soil microbiome for selection of polyethylene terephthalate-transforming bacterial consortia (2024)
Mangroves are impacted by multiple environmental stressors, including sea level rise, erosion, and plastic pollution. Thus, mangrove soil may be an excellent source of as yet unknown plastic-transforming microorganisms. Here, we assess the impact of polyethylene terephthalate (PET) particles and seawater intrusion on the mangrove soil microbiome and report an enrichment culture experiment to artifi- cially select PET-transforming microbial consortia. The analysis of metagenome.assembled genomes of two bacterial consortia revealed that PET catabolism can be performed by multiple taxa, of which particular species harbored putative novel PET-active hydrolases. A key member of these consortia (Mangrovimarina plasticivorans gen. nov., sp. nov.) was found to contain two genes encoding monohydroxyethyl terephthalate hydrolases. This study provides insights into the development of strategies for harnessing soil microbiomes, thereby advancing our understanding of the ecology and enzymology involved in microbial-mediated PET transformations in marine-associated systems.